Fogalmak és jelentések a területi politika hatókörében - Kőszeghy, Attila (Tér és Társadalom, 1994)
The inductive way regional policy is a certain combination of the programs of the local governments, it's deductive measures lead from the governmental policy towards the levei of settlements. A decentralized regional policy comes probably into beeing not inductively but through the competition among the policies of several subcentres. Hungarian regional, policy has the characteristics of that of the 1980-s. Not only the uncoordinated operating and the absence of certain institutions mean a problem but unclarified basic expressions as well. The essay to help in clarifying the phrasal systems concerning regional processes and in mapping the scape of movements in regional policy. Regarding the author the increase of the significance of regional policy does not derive from the social responsiveness of the government. Assistance of the underprivileged regions lessens the cruelty of aggregating economy and the some time ensures votes. The central notion of the essay is that regional policy does not include the management of the regional precesses for example the controlling of the regional development, if it was a part of the regional policy. Regional policy is an attitude that influances the direction of the processes. It manifests itself in activity of regulation, distribution, developings and preparing lislation. Regarding the legislation Budapest has got no competitor in the Hungarian regional processes. He finds it wrong to bring into existence nearly twenty intermediate regionalpolitical centres just because counties are already existing.